Perencanaan Perawatan Mesin dengan Metode Markov Chain Guna Menurunkan Biaya Perawatan - M. Eartono; Ilyas Mas'udin (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
Problem often faced by a fertilizer bagging machine unit is the inegularity of machinemaintenance in which the machine is operated continuously until it damages and can not beoperated any longer. It will result in relatively high down time cost.To solvet his problem we propose a machine maintenance planing based upon data acquired by using Markov Chain Method.There are four types of maintenance we propose they are:l. Maintenance planing with corrective maintenance or high level of damage condition and preventive maintenance or mediurn le vel ofdamage condition.2. Maintenancep laningw ith correctivem aintenancfeo r high and medium level of damageconditiona ndp reventivem aintenancfeo r low levelo fdamagec ondition.3. Maintenance planing with corrective maintenance or high level of damage condition andpreventive maintenance or medium and low level of damage condition4. Maintenance planing with corrective maintenance or high and medium level of damage condition.To determine the best proposal that will be selected we use analysis of preventive maintenance cost and corrective maintenance cost that will result in expected cost for eachmachine.From the four proposals one with the least expected cost is chosen that is planing with corrective maintenance for high level of damage condition and preventive maintenance formedium and low level ofdamage condition.